Measurement report: Long-term assessment of primary and secondary organic aerosols in the Shanghai megacity throughout China's Clean Air actions since 2010 - H. Yu; Y. Chang; L. Cheng; Y. Duan; J. Hu (Atmospheric Chemistry and Physics)
A growing body of research has demonstrated the effectiveness of China's Air Pollution Prevention and Control Action Plan in controlling PM2.5 (particulate matter with an aerodynamic diameter ≤2.5 µm), pollution. However, there is a lack of long-term studies investigating the impact of these abatement policies on carbonaceous aerosols in PM2.5, particularly secondary organic carbon (SOC). Shanghai, as China's largest megacity and a prominent industrial hub, serves as a crucial gateway to the nation's rapid development, with a population exceeding 20 million. In this study, we conducted hourly online measurements of organic carbon (OC) and elemental carbon (EC) in PM2.5 in Shanghai from July 2010 to July 2017. The results revealed that the annual concentrations (mean ± 1σ) of OC and EC reached their peaks in 2013 (9.5 ± 6.4 and 2.7 ± 2.6 to 3.0 ± 2.3 and 2.7 ± 2.1 µg m−3). Subsequently, a consistent year-to-year decrease in both OC and EC concentrations was observed, mirroring the trend observed for PM2.5. Primary organic carbon (POC), the primary component of OC, accounted for an average of 65.6 %, displaying similar trends to OC. This finding indicates the effectiveness of primary emission control measures. However, the concentration of secondary organic carbon (SOC) did not decrease from 2013 to 2017, remaining relatively stable within the range of 2.7 ± 2.6 to 3.0 ± 2.3 µg m−3. When considering data from previous studies in Shanghai, concentrations of SOC did not exhibit a noticeable decline until 2018, coinciding with the implementation of measures targeting volatile organic compound (VOC) emissions. Seasonally, with the exception of 2011, OC and EC concentrations were highest during winter, likely influenced by unfavorable meteorological conditions and long-range transport. SOC displayed no distinct seasonal fluctuations, as its formation is influenced by both photochemical reactions and meteorological conditions. POC and SOC exhibited different diurnal patterns, but neither showed a significant weekend effect, suggesting limited reduction in anthropogenic activities during weekends. Furthermore, SOC concentrations exhibited simultaneous increases in summer, particularly when O3 concentrations exceeded 50 µg m−3, indicating that stronger oxidation reactions contribute to higher SOC concentrations. Our findings also revealed concentration gradients of SOC dependent on wind direction (WD) and wind speed (WS), with higher concentrations typically observed for winds originating from the southwest and northwest. Potential sources from distant regions were analyzed using the potential source contribution function (PSCF), indicating that the geographical potential source area is concentrated near the middle and lower Yangtze River.